Factors Determining Farmers’ Decision on Highly Pathogenic Avian Influenza Vaccination at the Small Poultry Farms in Western Java - N Ilham; M Iqbal (Faculty of Animal Science, Bogor Agricultural University, 2011)
Vaccination of highly pathogenic avian influenza (HPAI) is one of the control measures in poultry farm. There are several factors determining farmer's decision on the implementation of this vaccination. They are the type of poultry, the experience of farmers in the poultry farm, the pattern of poultry farm management, the role of poultry farm on household income, the scale of poultry farm, the mortality rate of poultry, the cost of medication, and the case of HPAI. The analysis result showed that two factors namely type of poultry and the role of poultry farm on household income had significant influence on farmer's decision to implement HPAI vaccination. In fact, the implementation of HPAI vaccination would be more effective in independent farms since the risk of this disease was single-handedly borne by farmers. Apart from that, the implementation of HPAI vaccination would also be more effective in farms that had never been infected by HPAI, particularly layer farms. Overall, HPAI vaccination would be more effectively implemented through supporting biosecurity measures in poultry farms.